2023
DOI: 10.1186/s13054-023-04563-x
|View full text |Cite
|
Sign up to set email alerts
|

Early hyperbaric oxygen therapy is associated with favorable outcome in patients with iatrogenic cerebral arterial gas embolism: systematic review and individual patient data meta-analysis of observational studies

Raoul A. Fakkert,
Noa Karlas,
Patrick Schober
et al.

Abstract: Background Iatrogenic cerebral arterial gas embolism (CAGE) caused by invasive medical procedures may be treated with hyperbaric oxygen therapy (HBOT). Previous studies suggested that initiation of HBOT within 6–8 h is associated with higher probability of favorable outcome, when compared to time-to-HBOT beyond 8 h. We performed a group level and individual patient level meta-analysis of observational studies, to evaluate the relationship between time-to-HBOT and outcome after iatrogenic CAGE. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…The interval from the time of the procedure till the start of HBOT is of paramount importance. 2 It has been shown that HBOT within 6 or 7 hours has a better chance of a good outcome than delayed treatment. 3,4 In this case there is no indication of the duration of the interval before hyperbaric treatment could be started.…”
Section: Dear Editormentioning
confidence: 99%
See 2 more Smart Citations
“…The interval from the time of the procedure till the start of HBOT is of paramount importance. 2 It has been shown that HBOT within 6 or 7 hours has a better chance of a good outcome than delayed treatment. 3,4 In this case there is no indication of the duration of the interval before hyperbaric treatment could be started.…”
Section: Dear Editormentioning
confidence: 99%
“…Unfortunately, with massive amounts of air in the cerebral circulation, the outcome can be expected to be bad in some instances, even with the best care and including immediate HBOT. 2 An important aspect of the HBOT in this instance would be information about the air in the mediastinum. Since there was no ongoing air leak in this case, the expectation is that HBOT would facilitate the resorption of the air in the mediastinum.…”
Section: Dear Editormentioning
confidence: 99%
See 1 more Smart Citation
“…It can be assumed that hyperbaric therapy itself reduces the size of gas bubbles in blood vessels by following Boyle’s Law, which states that the surface area and volume of a gas bubble are inversely proportional to pressure. However, hyperbaric oxygen therapy (HBOT) has proven to be more effective in endogenous or exogenous gas embolism ( Fakkert et al, 2023 ; Marsh et al, 2023 ). HBOT is the most common emergency therapy for embolism.…”
Section: Introductionmentioning
confidence: 99%